(untitled) (Kwasu International Journal of Educational Management and Leadership, 2026)
Secondary school teachers in Kajola Local Government Area of Oyo State are increasingly burdened by digital workload, leading to emotional exhaustion, stress, and reduced job satisfaction. However, limited empirical research has explored how Human Resource Management (HRM) strategies can mitigate burnout and improve teacher retention. This study examined the relationship between digital workload and teacher burnout, assessed the effect of burnout on retention, and evaluated the effectiveness of HRM strategies in enhancing teacher well-being. A descriptive survey design was adopted. The study population comprised 1,250 teachers across 16 public secondary schools, from which 250 (120 males, 130 females) were selected using stratified random sampling. Data were collected using a structured questionnaire tagged “Digital Workload, Teacher Burnout, and Retention Strategies Questionnaire” (DWTBRSQ) validated by experts and yielding high reliability (α = 0.80–0.87). Pearson’s correlation, regression analysis, and ANOVA were used for data analysis. Findings revealed a significant positive relationship between digital workload and teacher burnout, with emotional exhaustion, depersonalization, and reduced accomplishment as major symptoms. Burnout negatively predicted teacher retention, while HRM strategies including mentorship, workload reduction, and professional development were found effective in reducing stress and enhancing retention. Although gender-based differences were minimal, female teachers reported slightly higher workload concerns. The study concludes that addressing digital workload and institutionalizing HRM interventions are critical for improving teacher retention and well-being. It recommended workload balancing, digital literacy training, and psychological support programs to enhance teacher job satisfaction and sustainability in the education sector.